Detection of arcing fault of electrical systems - Nuhakim Razak Effendi (Nanyang Technological University, 2020)
Partial discharge is a form of electrical arcing that shows the sign of insulation degradation of an electrical system. Thus, early detection of arcing is necessary to monitor the health condition of the electrical system. Detection of partial discharge has been widely researched over the years for condition monitoring purpose. This final year project introduces a method of detecting arcing using an RF receiver. An algorithm has been developed to compute the number of occurrences of arcing detected. With this data, the degradation severity of the electrical system can be evaluated, and the health condition of the electrical system can be predicted. To test the method, an arcing generator was constructed to emulate the arcing from the electrical system. An in-house experiment was conducted to measure the frequency spectrum of the emulated arcing and finally, an RF receiver is chosen as a PD detection system.